THE RELATIONSHIP BETWEEN PREFERRED ANATOMY LEARNING MEDIA (ANATOMAGE AND CADAVER) AND STUDENTS' PRACTICAL SCORES - Mokhtar, Shulhana; Alyaa Zatira, Difa; Sodiqah, Yani; Beru Gani, Azis; Surdam, Zulfiyah (Universitas Kusuma Husada Surakarta, 2025)
Anatomical knowledge is essential for science and clinical skills. Learning outcomes can be influenced by the choice of learning media, such as the computer-based Anatomage and Cadaver-based methods. This study examines the relationship between students' preferred anatomy learning media and their practical exam scores. A correlative analytic method with a retrospective cohort approach was used, involving 372 medical students from the Faculty of Medicine, Muslim University of Indonesia, selected through purposive sampling. Inclusion criteria included students who had completed anatomy courses and participated in practical exams. Bivariate analysis using the Chi-Square test showed a significant relationship between preferred media and exam scores (p-value < 0.05). Students with a strong preference for Anatomage achieved a higher pass rate (95%) and demonstrated better comprehension of anatomical structures compared to those favoring cadaver-based learning. These findings emphasize the effectiveness of Anatomage as a learning tool in enhancing anatomy education. In conclusion, the choice of learning media significantly impacts practical exam performance, with Anatomage proving to be a highly effective medium.